Critical thinking/questioning skills a meta-model for cognitive development in management education - Whiteley, Alma; Levantard, M.; Anderson, Paul (Curtin University of Technology, 1995)
The paper presents a model for the critical questioning of organisational practices and theories. P.A.T.P. represents PHILOSOPHY, ASSUMPTIONS, THEORY AND PRACTICES. The aim is to develop skills of questioning through three levels. The first level is Interesting. The second level is Important. The third level is Critical. The paper presents the model using two contrasting philosophies of organisation, as expounded by F W Taylor and Stephen Covey. The paper presents the educational setting of MBA seminar, a series of presentations by international and professional experts. Following each presented seminar is the Critical Questioning Session. The student co-author presents the student learning process through two case examples. He applies the approach outside of the MBA seminar setting, showing an extension of his learning. As a meta-model, the application should span cultures and disciplines with the aim of making sense of rather than adding on.